Inspector Lewis. The pilot and complete 1st series [videorecording (DVD)] - Whately, Kevin; Fox, Laurence; Holman, Clare; Front, Rebecca; Dexter, Colin; Lewis, Russell, 1963-; Jobst, Marc; Plater, Alan, 1935-2010; Harding, Sarah (Masterpiece theatre (Television program), 2008)
Home from a two-year assignment in the British Virgin Islands, Inspector Robert Lewis, protégé of the legendary Inspector Morse, returns to Oxford, England in the series pilot, where he is teamed with a brilliant new partner, Detective Sergeant James Hathaway. Lewis barely makes it out of the airport before falling into his first murder investigation. But even if he solves the case, will his new boss still move him from the front lines to a training assignment? Next, Lewis and Hathaway return to the streets of Cambridge and the halls of Oxford University with three more mysteries to unravel. In Whom the gods would destroy, Detectives Lewis and Hathaway are thrown into a delicate murder case that implicates one of Oxford University's most prominent figures when an old classmate of his is found dead. In Old school ties, Lewis comes face to face with his past when the murder of bright young Jo Gilchrist pulls Lewis and Hathaway into a case driven by celebrity, scheming, and dangerous sexual politics. In Expiation, when a North Oxford housewife is found hanged, it appears to be an open and shut case of suicide. But the lack of a suicide note and the victim's seemingly perfect life leads Lewis to suspect foul play.